Can Diabetes Self-Management Program Improve Patients’ Knowledge? A Real Life Evaluation Study of Lebanese Diabetic Adults - El-Haddam, Abeer; Hallit, Souheil; Raad, Etwal Bou (Journal of Pharmacy Practice and Community Medicine)
Objectives: The objective was to assess the effect of the Advanced National Standards for DSME program in improving the knowledge of Lebanese elderly diabetic patients. Secondary objectives were to test the influence of pharmacist counseling on managing these patients’ lifestyle and assess health perceptions that affect diabetic patients for effective management through the Health Belief Model (HBM). Methods: This cross-sectional study, conducted from February until May 2016 in different community pharmacies, enrolled 206 patients. Results: All knowledge items scores increased significantly from pre to post counselling (p<0.05 for all variables). Female gender significantly increased the knowledge score (Beta= 0.625; p=0.001), whereas living with a family member significantly decreased the knowledge score (Beta= 0.975; p=0.02). Regarding patient perception on the health belief model, the susceptibility score was significantly and positively correlated with the severity score and the benefits score (r=0.259 and r=0.680) respectively, but negatively correlated with the barriers score (r= -0.290). Moreover, the severity score was significantly correlated with the benefits score (r=0.230), whereas the benefits score was significantly but negatively correlated with the barriers score (r= -0.311). Conclusion: This study has demonstrated that a formal diabetes education program can effectively increase patients’ diabetes knowledge and will heighten patient knowledge about the disease and its complications.
Keywords: DSME; Health belief model; Education; Program; Diabetes mellitus